Can environmental regulations be compatible with higher international competitiveness? Some new theoretical insights - Savas Alpay (Fondazione Eni Enrico Mattei (FEEM), 2001)
Recently, the conventional view that stricter environmental regulations at home will affect the international competitiveness of the domestic firms negatively, has been challenged under the conditions that the regulated firms engage in innovation and that the environmental regulation is incentive-based. (This revisionist idea is known as the Porter hypothesis.) The considerable amount of empirical work in this literature as summarised in Jaffe and et al (1995) has not been able to generate evidence for either of these two views. Theoretical work is relatively limited and does not give much credit to the Porter hypothesis. We present some pro-revisionist theoretical evidence in a two-country model which incorporates Tradable Emissions Permit as environmental regulatory regime. In such a model, firms subject to stricter environmental regulation can offset regulatory costs through innovation and/or permit revenues by abating more and selling extra permits. Finally, as a new idea, we suggest that consumers may have preference for the good that is produced in a relatively cleaner way, and thus, imposition of higher environmental standards at home can increase the demand for domestic production, and opens up a road towards increased competitiveness. Incorporation of this idea into our model brings further evidence for revisionist school.
Keywords: 330; Umweltstandard; Emissionshandel; Internationaler Wettbewerb; Innovation; Theorie